Fuzzy Analytical Hierarchy Process (FAHP) for Evaluating Knowledge Areas of Advanced Certificate in Engineering Taught in South Africa - Maduna, Lusiwe; Ilunga, Masengo; Dube, Zakithi (Journal of systemics, cybernetics and informatics, 2024)
In order to evaluate the consistency of the knowledge areas (KAs) covered in the advanced certificate in engineering (AdvCertEng) course, this study used the Fuzzy Analytic Hierarchy Process (FAHP) technique. Both universities of technology and comprehensive universities in South Africa offer this subject. The primary requirements that an engineering programme should meet for the purposes of creating and implementing FAHP, are knowledge areas. The opinions of experts and decision-makers are prone to some subjectivity, imprecision, even some uncertainty and ambiguity, which results in fuzziness. Triangular fuzzy numbers (TFN1) between (1,1,1) and (9,9,9) are used to establish fuzzy pairwise comparisons between criteria on a qualitative level, whilst FAHP is used to calculate the weights of the criterion on a quantitative one. In this investigation, TFNs linked to a fuzzy distance from the crisp values of 1 are employed, and the related FAHP is denoted as FAHP1. The credit weight for each knowledge area is then calculated uniformly using the same method. AdvCertEng's existing knowledge area credit weights were generally confirmed using FAHP1. FAHP and ECSA's credit weights did, however, differ by minuscule amounts.